Orbital forcing of ice sheets during snowball Earth - Ross N. Mitchell (Nature Portfolio, 2021)
Reconciling the Snowball Earth hypothesis with sedimentological cyclicity has been a persistent challenge. A new cyclostratigraphic climate record for a Cryogenian banded iron formation in Australia provides evidence for orbital forcing of ice sheet advance and retreat cycles during Snowball Earth.